2020
DOI: 10.1007/s10792-020-01552-9
|View full text |Cite
|
Sign up to set email alerts
|

Agreement of white-to-white measurements with swept-source OCT, Scheimpflug and color LED devices

Abstract: Purpose To assess the interchangeability of different devices for measuring white-to-white (WTW) distance. Methods WTW distance was measured in 53 eyes of 53 patients using Anterion swept-source optical coherence topographer (SS-OCT), IOLMaster 700 SS-OCT, Pentacam HR Scheimpflug and Cassini color LED. Statistical analysis was done by means of the Friedman test and the post hoc Tukey test. The Bland-Altman analysis was applied to carry out pairwise comparisons with the average difference, 95% confidence interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 25 publications
3
21
1
2
Order By: Relevance
“…Bland-Altman plots were also constructed using the LoAs to compare both devices. Sample size calculation was based on recent studies that have analyzed agreement between AS-OCT and Scheimpflug devices [6,7]. For a 2-sided level of significance (α) at 0.05 and power (β) of 80%, the sample-size calculation indicated that a minimum of 50 participants was required to detect a difference of 0.1 µm in all measurements.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Bland-Altman plots were also constructed using the LoAs to compare both devices. Sample size calculation was based on recent studies that have analyzed agreement between AS-OCT and Scheimpflug devices [6,7]. For a 2-sided level of significance (α) at 0.05 and power (β) of 80%, the sample-size calculation indicated that a minimum of 50 participants was required to detect a difference of 0.1 µm in all measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Posterior Kf, Ks and Km differed significantly between devices, but mean differences were small and clinically irrelevant. Several studies have compared the performance of Anterion and other devices [6][7][8][9][10], but only one has provided agreement for posterior corneal surface readings [8]. Overall, for biometric measures, Anterion seems to be more interchangeable with other OCT devices such as CASIA or IOL-Master 700.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The recently developed ANTERION (Heidelberg Engineering, Heidelberg, Germany) is a highresolution swept-source optical coherence tomography (SS-OCT) device that provides a variety of anterior segment metrics, including anterior, posterior, and total corneal curvatures, as well as HOAs with high resolution, speed, providing an axial length, which calculates the IOL power as well. The high repeatability of anterior segment measurements including HOAs and axial length in ANTERION, has been reported [16][17][18], and the interchangeability in corneal curvature, WTW, pupil diameter, and ACD between other devices such as IOL Master 700 (Carl Zeiss, Jena, Germany), Pentacam (Oculus Inc., Wetzlar, Germany), and Cassini II (i-Optics, Den Haag, Netherlands) have been studied [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%